EVALUASI KINERJA SATUAN POLISI PAMONG PRAJA DALAM PELAKSANAAN RAZIA MINUMAN KERAS DI KOTA SERANG - Imelda Apriliani; Waseh, Hasuri; Rahmawati, Rahmawati (LPPM STIA Banten, 2024)
The purpose of this research is to find how the performance evaluation of the pamong praja police unit in the implementation of liquor raids in Serang City. In this research, the author uses a qualitative descriptive method. Researchers use observation, interviews, and documentation to collect data. The data ovtained is then analyzed through Data Reduction, Data Display, and Conclusion Drawing/Verification. The findings show that: Coordination before the curbing operation. In relation to coordination before the curbing operation, Satpol PP Serang City has coordinated with the PPNS, urban village, sub-district and neighborhood. Implementation of Standard Operating Procedures. In the Implentation of the SOP, the Serang City Civil Service Police Unit ini quite fully implementing the applicable SOP. in the implementation of operations to supervise and control the circulation of alcoholic beverages, there has never been rejection/resistance from violators. The initial report is one form of accountability of the Serang City Civil Service Police Unit which carries out a report after the implementation of an operation and accountability by the Serang City Civil Service Police Unit is an internal evaluation to dsicuss strategies for implementing better operations in the future so that accountability can be said to be good.